Komunikasi Nabawi Sebagai Asas Panduan Interaksi Media Sosial - Syed Mohammad Hilmi Syed Abdul Rahman; Muhammad Hazim Mohd Azhar; Che Zarrina Sa'ari; Mohd Anuar Ramli; Azah Anir Norman; Mohd Anuar Mamat (USIM Press, 2024)
Journal of Hadith Studies Voluem 8 No.2 Page (59-70)